Maintaining the quality and antioxidant capacity of ‘hass’ avocados after applying 1-methylcyclopropene (1-MCP) - Cábia, Nathalie C. [UNESP]; Daiuto, Érica R. [UNESP]; Vieites, Rogério L. [UNESP]; Smith, Robert E. (Bentham Science Publishers, 2014)
'Hass' avocados were submitted to post-harvest treatment with 0.060, 0.089 and 0.119 g 1-methylcyclopropene, (1-MCP) in 25 mL water, placed in 186 L boxes and refrigerated at 10 ºC±1 and 90±5% relative humidity. They were analyzed after 0, 3, 6, 9, 12 and 15 days of storage for weight loss, respiratory activity, titratable acidity (TA), soluble solids (S), index of maturation, pH, total phenols, antioxidant activity by the DPPH method and enzyme activities (polygalacturonase, PG, pectin methyl esterase, PME, and polyphenol oxidase, PPO). Also, on the 15th day, the fruits were removed from the refrigerator and stored for three more days at room temperature, to simulate commercial conditions and analyzed on the 18th day. Application of 1-MCP blocked the respiratory activity of the fruits. Doses of 0.089 and 0.119 g of 1-MCP did the best job of maintaining firmness, while minimizing soluble solids, indicating that the ripening process was slowed down.
Keywords: 1-methylcyclopropene; Hass avocados; Pectin methyl esterase; Polygalacturonase; Respiratory activity; Weight loss